BETWEEN ARTEMISININ AND DERIVATIVES WITH NEURAMINIDASE: A DOCKING STUDY INSIGHT - Pratama, Mohammad Rizki Fadhil; Gusdinar, Tutus (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: This study aims to find the relationship between artemisinins and neuraminidase (NA) with molecular docking study and also to determine the most potent NA inhibitor from artemisinin and derivatives. Methods: All ligands were sketched and optimized using Gaussian 03W with Hartree-Fock method basis sets 6-311G. Molecular docking was performed using AutoDock 4.2.3 toward NA in complexes with oseltamivir as co-crystal ligand. The main parameters used were the free energy of binding (Î”G) and dissociation constant (Ki) as affinity marker. Results: Artesunate provided most negative free Î”G and lowest Ki toward NA with âˆ’9.55 kcal/mol and 100.66 nM, respectively. Artesunate shows higher affinity than oseltamivir with interactions between artesunate and amino acids at position 246 had important influences on artesunate affinity toward NA from H5N1. Conclusion: In silico molecular docking results indicated that artesunate could be considered as NA inhibitor and should be potential to be developed as anti-influenza particularly to H5N1 with oseltamivir resistance.